Effect of Management of Performance Reward Systems on Subordinatesâ Satisfaction with Job in Malaysian Fire and Rescue Department - Ismail, Azman; Ishak, Yusniati; Abdullah, Anis Anisah (Bina Nusantara University, 2017)
This research was to measure the correlation between management of performance reward systems on subordinatesâ satisfaction towards the job. A survey method was utilized to collect data from subordinates who worked at the headquarters of fire and rescue departments in Malaysia. The outcomes of SmartPLS path model analysis display two important findings. First, the implementation of information delivery and performance assessment in handling performance reward systems have enhanced subordinatesâ intrinsic job satisfaction, but the implementation ofinvolvement hypothesized performance reward systems has not enhanced subordinatesâ intrinsic job satisfaction. Second, implementation of information delivery, involvement and performance assessment in handling performance reward systems have also enhanced subordinatesâ extrinsic job satisfaction.